South African budget 2018 : walking a fiscal tightrope - Schaling, Eric, 1962-; Hobbs, Jacklynne (London : Wits Business School, 2017)
In December 2017, as South Africa's minister of finance, Malusi Gigaba, and the Treasury continued putting together the country's 2018 budget, the country seemed perilously close to a fiscal cliff. Dismal economic growth and failures to contain government spending threatened to push the national debt to unsustainable levels - a situation compounded by public mismanagement and pervasive corruption in the form of "state capture" Gigaba had to find a way of halting the decline of South Africa's finances while ensuring that the fiscus continued in its central role of supporting the poor.
Originally Published In Schaling, E., & Hobbs, J. (2017). South African Budget 2018: Walking a Fiscal Tightrope. WBS-2017-15. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Budget -- South Africa; Finance, Public -- South Africa; South Africa -- Economic conditions